Implementasi Patient Safety di Pelayanan Anak Rumah Sakit Umum Haji Medan Tahun 2019 - Verawaty Sari Simamora; Zulfendri Zulfendri; Roymond H Simamora; Puteri Citra Cinta Asyura Nasution (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2020)
The complexity of diversity, relationships, variety and specialization can provide more opportunities for mistakes, one of which is in the children's hospital services. Based on patient safety incident report data at Rumah Sakit Umum Haji Medan in January 2018 to October 2018, it is known that child care is the unit with the highest number of patient safety incidents compared to other units at 37 incidents. Implementation of patient safety by officers in children's services is the main focus that must be considered its role to prevent the occurrence of patient safety incidents. This research is a qualitative research that aims to see the extent of the implementation of patient safety in child care at Rumah Sakit Umum Haji Medan from the description of the role of health workers involved in child care, namely the role of the head of a child's SMF, the role of a pediatrician, and the role of a child nurse. Data collection was carried out by in-depth interviews with 7 informants and through observation. The results showed the implementation of patient safety in children's services has not been running optimally. This is because not all health workers in child services, namely the head of the child's SMF, pediatricians and child nurses do their part in the patient safety system. The roles carried out are still focused on the standards of each profession. It is expected that routine socialization on the implementation of patient safety, the implementation of special meetings and discussions to study the patient safety system and the existence of patient safety drivers in child care designated as the person responsible for moving every officer to implement patient safety. Keywords: Implementation, Children's Services, Patient Safety